Turning Straw to Gold: Mobilising Symmetry in Responsible Research and Innovation. (July 2020) - Mamidipudi, Annapurna; Frahm, Nina
This article aims to reflect on the role of Science, Technology and Society (STS) research(ers) in co-constructing Responsible Research and Innovation (RRI) in the Global South. By reporting on RRI research in the Global South, here the Indo-Dutch NWO-MVI project on rice straw burning in Punjab, we make an argument for approaching RRI as a symmetric process of knowledge production mobilised by local actors and researchers alike. For STS researchers to responsibly engage with local innovation systems, their activities need to go beyond knowledge provision and towards facilitating the ownership and circulation of local meanings and means to responsibly innovate. Rather than understanding RRI as a fixed framework to govern innovation practices, this article reflects on RRI as an approach that combines research with intervention. We propose that following the principle of symmetry can turn RRI into a productive tool for the mobilisation of embedded local principles that can organise innovation systems in a responsible way. In particular, symmetry allows the re-location of meanings and practices of innovation as well as the re-negotiation of multiple notions of responsible governance.